2008
DOI: 10.1080/07315724.2008.10719674
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Fish Oil, Flaxseed Oil and Hempseed Oil Supplementation on Selected Parameters of Cardiovascular Health in Healthy Volunteers

Abstract: From a consumer's perspective, ingesting 2 capsules of any of these oils in an attempt to achieve cardiovascular health benefits may not provide the desired or expected result over a 3 month period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
102
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(114 citation statements)
references
References 42 publications
8
102
1
3
Order By: Relevance
“…It is important to note that in this study by Wallace et al, subjects consumed 3.5 g ALA per day which is only B60% of the dosage used in the present investigation. The results of that study are consistent with work of Kaul et al (2008), which showed that supplementation of the diet with B1 g/day of ALA as flaxseed oil resulted in only a transient increase in plasma ALA over a 12-week experimental intervention. These studies would suggest that a dose of 44 g/day is required to achieve significant increases in ALA.…”
Section: Discussionsupporting
confidence: 81%
“…It is important to note that in this study by Wallace et al, subjects consumed 3.5 g ALA per day which is only B60% of the dosage used in the present investigation. The results of that study are consistent with work of Kaul et al (2008), which showed that supplementation of the diet with B1 g/day of ALA as flaxseed oil resulted in only a transient increase in plasma ALA over a 12-week experimental intervention. These studies would suggest that a dose of 44 g/day is required to achieve significant increases in ALA.…”
Section: Discussionsupporting
confidence: 81%
“…Another trial saw no effect on serum oxidised LDL concentrations after 10 weeks intervention with 4 g/d ALA from flaxseed [103]. The difference in findings of the latter three studies compared with the study of Sodergren et al [143], perhaps reflecting the low intakes of PUFAs used. Overall, these studies suggest that ALA intakes up to 6 times greater than that found in the typical UK diet (~1.5/d) do not significantly alter markers of blood lipid peroxidation when consumed for relatively short periods of time.…”
Section: Low-density Lipoprotein Oxidationcontrasting
confidence: 49%
“…However, some studies in which ALA intake was increased did not find a significant effect on collagen-induced platelet aggregation [129,228]. Kaul et al also reported that flaxseed oil supplementation (providing 1 g/d ALA) induced no significant change in collagen or thrombin stimulated platelet aggregation [143], although this is a much lower dose of ALA than used in other studies looking at these outcomes. Overall, it is not clear whether high ALA intakes reduce platelet aggregation or not, due to the inconsistencies in findings from different studies.…”
Section: Platelet Aggregation and Haemostasismentioning
confidence: 88%
“…Ground flaxseed has been shown to reduce cholesterol levels (Bloedon et al, 2008) whereas feeding of ALA (Alpha linolenic acid) in the form of flaxseed oil fed to human beings (Kaul et al, 2008) didn't alter lipid levels. Flaxseed contains at least three components that are of health interest: soluble fibers or mucilage (Diederichsen, 2006); high amounts of ALA (Choo, 2007); and the plant lignin secoisolariciresinol diglucoside (Johnsson et al, 2000).…”
Section: Resultsmentioning
confidence: 99%